Fundamental aspects and technological applications of bubbling for non-metallic inclusion removal and slag foaming in steelmaking - Falsetti, Luís Otávio Zaparoli (Universidade Federal de São Carlos, 2025)
Bubbles are applied in a wide range of industrial processes, such as ore flotation, aluminium foaming and even texture control in foods. In steelmaking, gas bubbles are typically injected into the liquid steel to remove non-metallic inclusions and into the slag to induce its foaming in the electric arc furnace (EAF). Currently, challenges in the steel industry are driven by both the sector's sustainability and the demand for steels with improved properties, particularly in achieving greener and cleaner steels. EAF slag foaming and non-metallic inclusion removal using bubbling through porous ceramic plugs are closely linked to these challenges and can benefit from a better understanding of the fundamentals involved in the use of gas bubbles. Therefore, this doctoral thesis investigates the fundamental mechanisms and technological applications of gas bubbling in steelmaking, specifically targeting the removal of non-metallic inclusions and the control of slag foaming. The study is divided into three main approaches: bubble generation, inclusion flotation kinetics, and slag foam stability. First, the influence of the purging plug's surface wettability on bubble size was modelled, establishing a combined model that delineates pore-dominated and material-dominated bubbling regimes. It was demonstrated that although non-wetting ceramic surfaces prevent liquid steel infiltration, they generate bubbles larger than 10 mm, which are less effective at removing inclusions. Second, physical simulations in a tundish water model evaluated the flotation of hydrophobic and hydrophilic particles. The results identified a trade-off where smaller bubbles (0.6 mm) achieved higher removal efficiencies, but slower removal rates than larger bubbles (1.1 mm). Finally, a framework coupling computational thermodynamics (FactSage) and machine learning (GlassNet) was developed to predict slag foamability. This framework was applied to investigate defoaming agents, identifying a by-product of the continuous casting as a potential alternative to fluorine-based additives for accelerating foam collapse by reducing the slag's effective viscosity.
Fundamental aspects and technological applications of bubbling for non-metallic inclusion removal and slag foaming in steelmaking
Keywords: non-metallic inclusion; purging plug; slag foaming; smart bubbles; steelmaking; inclusão não metálica; plugue poroso; espumação de escória; bolhas inteligentes; aciaria; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; 9. Indústria, Inovação e Infraestrutura